Persepsi Siswa Terhadap Praktik Pelanggaran Hak Asasi Manusia Di Media Sosial: Pada Kalangan Pelajar SMA - Nasution, Dita Maisaroh; Elzenia, Alia Dwi; Salfira , Belsa; Musryid, Ekmal; Putri, Nabila Ananda; Jefita, Nadely Syarrova; Athifa, Naela; Tahmi, Tamala; Yuliana; Hambali (Hakim: Jurnal Ilmu Hukum dan Sosial, 2025)
This study explores high school students' perceptions and awareness of human rights violations (HRV) on social media. Using a mixed-method approach involving interviews and questionnaires with 100 students from five schools in Pekanbaru, the research reveals that the majority of students recognize various HRV issues such as hate speech, cyberbullying, discrimination, and privacy violations, and understand their impacts. Approximately 75% of students feel responsible to report HRV incidents, though some hesitate due to fear or perceived helplessness. While most students are familiar with the term HR, only 60% can accurately define protected rights like privacy and freedom from bullying. The average awareness score is 7.5 out of 10, influenced by socio-economic background and parental education. Findings indicate that 70% have witnessed hate speech, 55% have experienced or observed cyberbullying, and 60% acknowledge that spreading hoaxes infringes on the right to information. A significant majority (85%) agree that HR education should be integrated into school curricula. Despite high awareness levels, students' understanding of the boundaries and consequences of digital expression remains limited, highlighting the need for ongoing educational interventions and curriculum development in digital ethics and human rights. The study emphasizes the importance of continuous literacy programs and recommends further research with broader geographic scope and qualitative methods to deepen understanding.